Forms of Implementing Corporate Social Responsibility in Indonesian Sharia Banks - Reza Riznando; Yopi Yopi; Gandi Agung Pranata (Sharia Economic and Management Business Journal (SEMBJ), 2024)
Corporate Social Responsibility or what is often referred to as Corporate Social Responsibility (CSR) is almost implemented by all companies, in this case, the Islamic Banking industry where the company is committed to quality development and community welfare. CSR can be implemented in the form of corporate social activities as stipulated in Law Number 40 of 2007 concerning the implementation of CSR/corporate social responsibility. This research has several objectives, one of which is to find out the forms of CSR (Corporate Social Responsibility) carried out by Islamic banks. In addition, this research also shows the areas that are the focus of the company in the CSR program.